3D Nitrogen and Sulfur Co-Doped Graphene/Integrated Polysaccharides for Electrochemical Recognition Tryptophan Enantiomers. Issue 12 (1st January 2019) - Yang, Xing; Niu, Xiaohui; Mo, Zunli; Wang, Jia; Shuai, Chao; Pan, Zhao; Liu, Zhenyu; Liu, Nijuan; Guo, Ruibin
Abstract : Polysaccharides based on carboxymethyl β-cyclodextrin (β-CD-COOH) and chitosan (CS) were synthesized by amidation reaction between -COOH on β-CD-COOH and -NH2 on CS to develop the electrochemical sensors. The sensor was constructed by combining the advantages of the polysaccharide CS-β-CD and the guest molecule and the 3D N, S co-doped graphene (NSG). CS-β-CD was used as chiral selector can provide a large number of chiral sites and NSG served as base material can improve electrochemical signal. The enantioselectivity of the chiral platform for tryptophan (Trp) enantiomers was studied by differential pulse voltammetry (DPV). NSG/CS-β-CD modified GCE showed higher electrochemical signal for L-Trp than D-Trp. When forming diastereoisomeric enantiomer-selector complexes between Trp isomers and NSG/CS-β-CD, there showed different steric hindrances, which made it easier for L-Trp to penetrate the modified electrode film to reach the electrode surface, thus producing a larger peak current. UV-vis further proved that CS-β-CD has higher binding energy to D-Trp. In addition, the proposed electrochemical sensor can be used to detect actual samples. Therefore, the proposed electrochemical chiral interface can be used as a promising chiral sensing platform for enantiomer recognition of chiral compounds.